Bridging Geography and Education for Sustainable Development: A Korean Example. Issue 1 (2nd January 2017) - Gress, Douglas R.; Tschapka, Johannes M.
Abstract : There is an apparent disconnect between geography and education for sustainable development (ESD), with geography underrepresented in publications and curricula related to sustainability though the discipline embraces the need to foment positive change. To bridge this schism, this article introduces advances in education for sustainable development (ESD-2) and a three-dimensional key competence-based model that can be deployed in tandem with economic geography theory. Deploying the theme of solar PV in Korea, a competency-based lesson planning exercise is presented to demonstrate the potential for this learning paradigm to generate agency and empower change for a sustainable future.